PEMANFAATAN LIVE STREAMING TIKTOK SEBAGAI STRATEGI PEMASARAN PADA BYME HIJAB STORE JEMBER - Faizal, Ahmad; Wijayati, Cici; Hadi Mubarok, Achmad (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to analyze the marketing strategy implemented by Byme Hijab Store Jember through the live feature on the Tiktok social media application, with a marketing mix approach and sharia marketing principles. The research method used is qualitative descriptive and SWOT analysis to identify supporting and inhibiting factors, with the main sources being the owner of the convection and the person in charge of marketing. The results of the study show that Byme Hijab Store Jember has succeeded in utilizing the four variables in the marketing mix (product, price, place, and promotion) while maintaining a commitment to sharia principles. Some of the main supporting variables are product quality and the use of social media, while inhibiting variables include limited resources and tight competition. In conclusion, despite the challenges, the strategy implemented by Byme Hijab Store Jember has a major impact on the profits they get.